Comfort Food pada Lansia di Panti Werdha Salatiga - Rosiana Eva Rayanti; Stephanie Martha Silahoy; Catherine Natawirarindry (Jurnal Keperawatan, 2023)
Background: Comfort food is a food that is directly selected by the elderly on the basis that the food is delicious, pleasant texture, like crispy and the aroma of food is more sweet or salty than sour and bitter. One way to increase appetite and enjoyment when consuming food, through a Comfort food approach. Research Objective: Describe Comfort food for the elderly in Salatiga Nursing Home. Research Method: This study uses descriptive qualitative research methods, the criteria for participants are elderly women over the age of 60 years who live in nursing homes and are still able to communicate. The number of study participants was 12 elderly people at Merbabu Nursing Home, White Cross Nursing Home and Maria Martha Elderly House. Results: Based on the results of this study, it was found that the elderly living in Maria Martha Nursing Home, Merbabu Nursing Home and White Cross Nursing Home, had impaired nutritional status or Mini Nutritional Assessment (MNA) which was at risk of malnutrition (six people).